DEAD-box RNA helicase 21 negatively regulates cytosolic RNA-mediated innate immune signaling - Li, Jia; Fang, Puxian; Zhou, Yanrong; Wang, Dang; Fang, Liurong; Xiao, Shaobo (Frontiers in Immunology, 2022)
DEAD-box RNA helicase 21 (DDX21), also known as RHII/Gu, is an ATP-dependent RNA helicase. In addition to playing a vital role in regulating cellular RNA splicing, transcription, and translation, accumulated evidence has suggested that DDX21 is also involved in the regulation of innate immunity. However, whether DDX21 induces or antagonizes type I interferon (IFN-I) production has not been clear and most studies have been performed in overexpression and siRNA knockdown experiments. In this study, we generated DDX21 knockout cell lines and found that knockout of DDX21 enhanced Sendai virus (SeV)-induced IFN-β production and IFN-stimulated gene (ISG) expression, suggesting that DDX21 is a negative regulator of IFN-β. Mechanistically, DDX21 competes with retinoic acid-inducible gene I (RIG-I) for binding to double-stranded RNA (dsRNA), thereby attenuating RIG-I-mediated IFN-β production. We also identified that the 217–784 amino acid region of DDX21 is essential for binding dsRNA and associated with its ability to antagonize IFN production. Taken together, our results clearly demonstrated that DDX21 negatively regulates IFN-β production and functions to maintain immune homeostasis.